2021
DOI: 10.1029/2021gc009805
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Brittle‐Ductile Oscillations Recorded in Exhumed High‐Pressure Continental Units: A Record of Deep Episodic Tremor and Slow Slip Events in the Northern Apennines

Abstract: Apennines and preserves brittle/ductile structures  During subduction local dehydration reactions triggered transiently high pore pressure in continental metasediments at ~1.1 GPa and 350 °C  Coeval carpholite dilational shear veins and mylonitic foliation cab be a geological record of deep episodic tremor and slow slip events Accepted ArticleThis article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 102 publications
(239 reference statements)
3
27
0
Order By: Relevance
“…Tectonic foliations across the MRC, ranging from subhorizontal to gently NE and SW dipping, define an antiformal structure, which is common in other exposures of the TMC (e.g., Carmignani et al, 1994; Carmignani & Kligfield, 1990; Molli & Vaselli, 2006; Papeschi et al, 2017). The observed HP–LT chloritoid‐bearing parageneses are compatible with similar Alpine assemblages that have been described in nearby TMC exposures, for example, in the Argentario (Theye et al, 1997), and the Mid‐Tuscan Ridge (Brogi & Giorgetti, 2012; Giorgetti et al, 1998; Giuntoli & Viola, 2021) (Figure 1a). The RSCM thermometry (average peak T of 382 ± 8°C) does not support a Variscan tectono‐metamorphic inheritance within the MRC, because its thermal structure is not compatible with the hotter environments (HT greenschist to amphibolite facies conditions) documented for the Variscan metamorphism in the region (e.g., Franceschelli et al, 2004; Lo Pò et al, 2016; Pandeli et al, 2005).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Tectonic foliations across the MRC, ranging from subhorizontal to gently NE and SW dipping, define an antiformal structure, which is common in other exposures of the TMC (e.g., Carmignani et al, 1994; Carmignani & Kligfield, 1990; Molli & Vaselli, 2006; Papeschi et al, 2017). The observed HP–LT chloritoid‐bearing parageneses are compatible with similar Alpine assemblages that have been described in nearby TMC exposures, for example, in the Argentario (Theye et al, 1997), and the Mid‐Tuscan Ridge (Brogi & Giorgetti, 2012; Giorgetti et al, 1998; Giuntoli & Viola, 2021) (Figure 1a). The RSCM thermometry (average peak T of 382 ± 8°C) does not support a Variscan tectono‐metamorphic inheritance within the MRC, because its thermal structure is not compatible with the hotter environments (HT greenschist to amphibolite facies conditions) documented for the Variscan metamorphism in the region (e.g., Franceschelli et al, 2004; Lo Pò et al, 2016; Pandeli et al, 2005).…”
Section: Discussionsupporting
confidence: 85%
“… Pourteau et al (2014) showed that extensive, continuous, and discontinuous zoning patterns can develop in (Fe, Mg)‐chloritoid–carpholite parageneses due to fractionation of elements in the chloritoid cores from the bulk during the metamorphic evolution. Indeed, (Fe, Mg)‐carpholite commonly occurs in syn‐metamorphic quartz veins in the Verrucano Group metasediments of the TMC (e.g., Brogi & Giorgetti, 2012; Giorgetti et al, 1998; Giuntoli & Viola, 2021; Rossetti et al, 1999; Theye et al, 1997). We could, in principle, infer its former presence also in the MRC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Along subduction plate boundaries, localized embrittlement within otherwise aseismic regions may be triggered by either or a combination of locally reduced effective stresses (e.g., Fagereng, Diener, Meneghini, et al., 2018; Gao & Wang, 2017; Giuntoli & Viola, 2021; Shelly et al., 2006; Yardley, 1983), or locally increased shear stress (Beall et al., 2019a; Sibson, 1980). Direct constraints on the composition and internal geometry of plate boundary shear zones may provide insight into how and why variations in shear stress or effective stress occur.…”
Section: Introductionmentioning
confidence: 99%